Indikator Prinsip Penyalahgunaan Keadaan Dalam Pertimbangan Hakim Pada Putusan Mahkamah Agung Nomor 1395 K/PDT/2017 - Welda Aulia Putri; Anjar Sri Ciptorukmi Nugraheni (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This research aims to analyze the indicators of the principle of abuse of circumstances in the consideration of judges who give rise to legal consequences of the existence of abuse of circumstances in economic excellence in an agreement. The research method in this journal is normative legal research. The nature of research in this journal is prescriptive. The research approach used is the legislation approach and case approach. Primary legal materials in this journal, namely the Civil Code, jurisprudence, and court decisions. As for secondary legal materials, namely book literature, legal journals, and other relevant literature. The results of the study indicate that the case in Supreme Court Decision Number 1395 K/Pdt/2017 has proven that there is an abuse of circumstances in economic excellence.